PENGARUH PENGAWASAN ORANG TUA TERHADAP PERKEMBANGAN MORAL REMAJA DALAM PENGGUNAAN SMARTPHONE DI SMP IT CENDIKIA DI MASA NEW NORMAL - Roida Hazima; Junaidin (JURNAL PSIMAWA, 2020)
The purpose of this research is to determine the effect of parental supervision during the New normal on the moral development of adolescents. This study uses a quantitative approach. The sampling technique in this study using purposive sampling. The sample in this study amounted to 81 adolescents. The research data were obtained using research instruments in the form of two scales, namely the scale of parental supervision and the scale of moral development. The results showed that parental supervision had an effect on moral development in adolescents with a significance value of Sig. 0.000 (Sig. <0.05) and R Square of 0.158, which means parental supervision has an effect of 15.8%, while 84.6% is influenced by other variables not examined in this study. Parental supervision is in the sufficient category with the highest aspect being the active supervision aspect Meanwhile, moral development is in the good category with the highest aspect being the cognitive aspect.